Post-discharge use of opioids, psychostimulants, and treatment medications following residential opioid discontinuation with NET Device™ monotherapy - Greenwald, Mark K.; Arfken, Cynthia L.; Winston, Joe R. (Frontiers in Psychiatry, 2025)
BackgroundMedical devices offer an established therapeutic approach for managing the transition from polysubstance use to abstinence, but little is known about longer-term outcomes.AimDetermine opioid and psychostimulant use over 12 weeks post-discharge following residential use of the NET Device™ or sham among participants with opioid use disorder (OUD).DesignTwelve-week observation following randomized controlled trial of active NET Device (n = 53) versus sham (n = 55) as monotherapy during residential opioid discontinuation in 103 participants who completed >1 post-discharge interview (95% follow-up rate).Setting and participantsAdults with OUD (50.0% with psychostimulant use) recruited at admission from 4 residential addiction treatment facilities in Kentucky.MeasuresPercentage of days using illicit opioids and psychostimulants as well as medications for OUD (MOUD) from weekly timeline follow-back interviews.ResultsActive and sham device groups reported similar rates of MOUD use and illicit opioid and psychostimulant use. In a planned secondary analysis, participants who self-administered active stimulation >24 hours (n = 23) compared to active <24 hours (n = 25), sham >24 hours (n = 21), and sham <24 hours (n = 34) reported significantly (p <.05) lower percentages of days using opioids (1.4% vs 7.4%, 6.8%, and 4.4% respectively) and psychostimulants (1.3% vs 4.1%, 6.7%, and 4.3% respectively) and MOUD (1.2% vs 20.7%, 11.3%, and 16.7% respectively).ConclusionsThe randomized groups did not differ on outcomes. However, participants who self-administered active NET Device stimulation >24 hours reported significantly fewer post-discharge days of opioid or psychostimulant use than those who self-administered active <24 hours or sham, but these findings need to be replicated.Clinical Trial Registration: ClinicalTrials.gov, identifier NCT04916600.